Dilodendron bipinnatum Radlk. ameliorates airway inflammation through multiple targets in a murine model of ovalbumin-induced allergic airway disease. (15th November 2018) - de Oliveira, Ruberlei Godinho; Miyajima, Fábio; Castilho, Geovane Roberto de Campos; Damazo, Amílcar Sabino; Macho, Antonio; Martins, Domingos Tabajara de Oliveira
Abstract: Ethnopharmacological relevance: Dilodendron bipinnatum Radlk., Sapindaceae, a tree of the Mato Grosso Pantanal, is popularly known as "mulher-pobre". The decoction or infusion of its inner stem bark is used for treating inflammatory conditions. Aim of the study: To determine if a 70% hydroethanolic extract of Dilodendron bipinnatum stem bark (HEDb) is able to reduce allergic airway inflammation in a murine model of ovalbumin (OVA)-induced allergic asthma. Material and methods: The inner stem bark powder was macerated in a 70% hydroethanolic solution (1:3 w/v) to obtain HEDb. The induction of experimental asthma was accomplished as follows: on days 1 and 10, Swiss mice were sensitized by an intraperitoneal injection of OVA (100 µg/mL) and aluminum hydroxide (10 µg/mL). From day 19 to 24, animals (n = 6/per group) were treated (p.o.) twice a day with either vehicle (distilled water), HEDb (20, 100 and 500 mg/kg) or dexamethasone (0.5 mg/kg). Sham group animals were intraperitoneally injected and challenged with saline solution (0.9%) instead of OVA and received distilled water orally instead of HEDb, whereas the other groups were challenged with OVA (3% in saline) by aerosolization. On day 25, bronchoalveolar lavage fluid (BALF) was collected for the quantification of total leukocytes, neutrophils, eosinophils, mononuclear cells and Th2 cytokines (IL-4, IL-5, and IL-13). The lungs were collected for histopathological analysis and blood was assayed to determine serum IgE levels. The anti-inflammatory activity of HEDb was additionally confirmed by a lipoxygenase (LO) inhibitory assay in vitro. Results: Compared to the sham group, the OVA group showed significantly greater numbers of total leukocytes, neutrophils, eosinophils, and mononuclear cells, as well as inflammatory cytokines in BALF, and also IgE in the serum. HEDb treated mice showed a significant decrease in inflammatory cell accumulation in BALF, with the maximum response observed at 500 mg/kg. Furthermore, the levels of IL-4, IL-5 and IL-13 in BALF, and of IgE in serum, were also considerably reduced as compared to the OVA group. The histopathological examination of the lungs of mice in the vehicle group showed a significant increase in hemorrhagic damage, mucus, perivascular and peribronchial inflammatory cell infiltrates, as well as mast cell degranulation compared to sham. HEDb (100 and 500 mg/kg) remarkably decreased all these parameters, presenting at the highest dose an anti-inflammatory effect comparable to that of dexamethasone (0.5 mg/kg). HEDb also had notable direct anti-inflammatory properties demonstrated by the inhibition of 15-LO activity in vitro (IC50 = 1.0–5.0 µg/mL). Conclusions: These results somewhat agree on the popular use of the inner stem bark of D. bipinnatum as a treatment for allergic asthma. The HEDb exhibits significant anti-inflammatory activity in the OVA-induced mouse model of allergic asthma, possibly due to the down-regulation of the Th2 responses and LO inhibition, resulting in improvements in all analyzed inflammatory parameters. Graphical abstract: